Antibacterial Compound Identification of Cayenne Pepper Leaf Extract (Capsicum frutescens L.) against Klebsiella pneumoniae and Cell Leakage Mechanism - Riri Fauziyya; Laela Hayu Nurani; Nanik Sulistyani (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Pneumonia is an acute inflammation of the pulmonary parenchyma that can be caused by Klebsiella pneumoniae. This study aims to determine the active fraction of cayenne pepper leaves on the growth of K. pneumoniae. Cayenne pepper leaf which previously defatted using n-hexane was macerated with 95% ethanol, then fractionated successively with dichloromethane, ethyl acetate and methanol. Ethanol extract and each fraction with concentration of 40% were tested for their antibacterial activity against K. pneumoniae using disc diffusion method (Kirby-Bauer). 1% amoxicillin was used as positive control and Dimethyl sulfoxide (DMSO) as negative control. The Minimum Inhibitory Concentration (MIC) of the most active fraction was then determined. Determination of antibacterial compound in the most active fraction was carried out by TLC-bioautography and followed by Gass Chromatography Mass Spectrophotometry. Cell leakage analysis was performed using UV spectrophotometry to detect the release of protein and nucleic acid, as well as Atomic Absorption Spectrophotometry was used to detect ion release of K+ and Ca2+. The results showed that the most active fraction against K. pneumoniae was the ethyl acetate fraction with MIC value of 10% and inhibition zone of 7.25±0.25 mm. TLC-Bioautography of ethyl acetate fraction with eluen n-hexane: ethyl acetate (6:4) obtained an active stain at Rf 0.12. Compounds having 94% similarity with 1-propanol, 2-amino was predicted as the active compound.